Establishing a repository of scientific publications as a step toward creating a unified scientific space in Ukraine - Vlodek, O. B.; Markevych, H. Yo.; Ostanina, N. V.; Bryazkalo, V. V.; Cheremenko, A. M.; Didenko, I. A. (Environment & Health, 2026)
The principle of Open Science provides for general access to scientific results, data and research methods, and also promotes transparency and collaboration in the scientific process. This, in turn, provides for open access to publications and data, open analysis, open materials, pre-registration and open collaboration. The creation of an electronic repository of scientific data of a research institution and its subsequent integration into national-level electronic archives is an important component of the development of a single scientific space in Ukraine. Purpose: to highlight the results of the creation of a pilot project of an open archive of scientific publications of the State Institution «O.M. Marzieiev Institute of Public Health of the National Academy of Medical Sciences of Ukraine». Methods: computer search methods (keyword search, semantic search) and computer modeling were used. Results. It was found that a National Repository of Academic Texts has been created in Ukraine, which closely cooperates with such well-known scientific institutions as the Taras Shevchenko National University of Kyiv, NTU «Igor Sikorsky Kyiv Polytechnic Institute», the National Academy of Pedagogical Sciences of Ukraine, the O.O. Bogomolets National Medical University. In order to constantly inform the target audience, useful materials are published on various issues, from administrative decisions adopted by the government and central authorities, discussions of draft documents, scientific events, to analytical materials of international organizations, best practices of open science and research data management, the use of AI technologies, academic integrity, and the popularization of scientific achievements. At the same time, the National Repository of Academic Texts does not represent such participants as the National Academy of Medical Sciences of Ukraine and its departmental research institutions, in particular the State Institution «O.M. Marzieiev Institute of Public Health of the National Academy of Medical Sciences of Ukraine». Conclusions. It has been proven that the presence of scientific publications on the official website of a research institution is not a sufficient condition for increasing their citation index. The necessary creation at the level of a research institution of an open archive of scientific publications of its scientists, and its integration into nationwide distributed electronic databases in which academic texts are accumulated, stored and systematized, will contribute both to increasing the authority of the institution in scientific circles and to the development of educational, scientific, scientific-technical and innovative activities of our state as a whole.